The researching and modeling of structures of mobile networks for providing of multiservice radio access - Klymash, Mychailo; Savchuk, Roman; Pozdnyakov, Pavel; Beshley, Mykola (Видавництво Львівської політехніки, 2012)
In this paper the method of granting of multimedia services to subscribers of mobile network which consists in the replacement of segment access has been proposed. The algorithm of radio resources management of convergent device of mobile communication technologies has been created.
Keywords: handover; technology; femtocell; resources; convergent device